2019
DOI: 10.1016/j.biombioe.2018.11.036
|View full text |Cite
|
Sign up to set email alerts
|

Biochar as a cheap and environmental friendly filler able to improve polymer mechanical properties

Abstract: This study reports about the use of Biochar derived from maple tree as a filler in Epoxy resin. Maple tree blocks were pyrolyzed in inert atmosphere at 600 °C and 1000 °C respectively and were characterized morphologically. The composite mechanical properties, i.e. stress-strain curves and related parameters (ultimate tensile strength, Young modulus, resilience, tensile toughness) were recorded as well as their friction coefficient. It is shown that at very low wt.% of the filler, the Young modulus is increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 99 publications
(70 citation statements)
references
References 16 publications
(15 reference statements)
2
60
0
Order By: Relevance
“…Recently, biochar (BC) has attracted increasing interest as far as its utilization as filler for polymer-based composites, either thermoplastics or thermosets, is concerned [19,20]. BC is usually obtained from the pyrolysis of agricultural and forestry wastes [21], and its structure can be tuned depending on the pyrolysis conditions; in particular, by adjusting the temperature and the oxygen flow, the degree of internal porosity and the presence of different functional groups anchored to the surface can be tailored [22].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, biochar (BC) has attracted increasing interest as far as its utilization as filler for polymer-based composites, either thermoplastics or thermosets, is concerned [19,20]. BC is usually obtained from the pyrolysis of agricultural and forestry wastes [21], and its structure can be tuned depending on the pyrolysis conditions; in particular, by adjusting the temperature and the oxygen flow, the degree of internal porosity and the presence of different functional groups anchored to the surface can be tailored [22].…”
Section: Introductionmentioning
confidence: 99%
“…Giorcelli et al . reported the use of high thermal treated biochar for the production of conductive epoxy composite while other studies reported the improvement of mechanical properties of biochar containing reinforced plastics . Recently, Bartoli et al .…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Giorcelli et al [63] proved the effectiveness of maple tree-derived biochar produced at 600°C and 1000°C, observing a drastic improvement of maximum elongation compared with neat resin.…”
Section: Fillersmentioning
confidence: 88%